Complex Arterial Pathology of Angiomyolipomas of Tuberous Sclerosis - Yeisley, Christopher D.; Tafreshi, Shima; Moirano, Joseph; Gandras, Eric; Siegel, David (International Journal of Angiology, 2022)
Based on observations at angiography, it was hypothesized that angiomyolipomas (AMLs) associated with tuberous sclerosis complex (TSC) have a more robust parasitic blood supply and require more complex embolization involving lower order vessels compared with the non-TSC patients' AMLs. This was a retrospective review of 71 patients who underwent angiography and embolization for renal AML at multiple centers within a single health system. All of the patients with TSC (11/11) were found to have “complex” tumor vascular supply. Of the patients with sporadic AML, 51/60 (85%) had “simple” tumor vascular supply. Sporadic cases with a complex tumor blood supply were larger tumors, with an average size of 11.5 cm. This study supports our hypothesis that AMLs associated with TSC have more complex tumor vascularity compared with sporadic lesions, and aims to better prepare interventionalists to deal with the complex cases.
Keywords: AML; tuberous sclerosis; tuberous sclerosis complex; tumor; embolization; complex tumor vascularity; hemorrhage